STUDIES ON CHARACTER ASSOCIATION AND PATH ANALYSIS IN RICE (Oryza sativa L.) - S. NARENDER REDDY, K. PARIMALA, CH. SURENDER RAJU, S. SUDHEER KUMAR and (The Journal of Research, PJTSAU, 2017)
An experiment was conducted to know the association between yield components and to assess their direct and indirect effects on grain yield in rice. The yield components such as number of productive tillers per plant and number of filled grains per panicle were found to be very crucial for high yields, as they exhibited significant positive correlations with grain yield per plant. The other important traits to be considered are plant height and panicle length. Generally, in rice, semi tall plant types (110-115 cm) with sturdy culm (non- lodging) would yield better than the dwarf ones. Path coefficient analysis revealed that number of filled grains per panicle exerted highest positive direct effect on grain yield followed by number of productive tillers per plant, 1000 grain weight, spikelet fertility (%) and days to 50% flowering at both phenotypic and genotypic level. Number of productive tillers per plant had positive indirect effects through all the yield components except 1000 grain weight.